Associations between emotion dysregulation dimensions and parenting behaviors in trauma-exposed African American mothers - Powers, Abigail (Child maltreatment, 2022)
Parenting behavior is key to understanding transmission of intergenerational trauma-related risk. Emotion dysregulation (ED) and psychological symptoms are associated with negative parenting behaviors, although their unique roles remain unclear. The current study examined associations of ED dimensions, depression, PTSD, and substance use with parenting behaviors in African American mothers. Participants included 98 mother-child dyads recruited from an urban hospital setting. Trauma exposure, ED, depression, substance use, and parenting behaviors (overreactivity, laxness, demandingness, warmth, corporal punishment) were assessed using self-report measures. PTSD was assessed using a semi-structured interview. Correlational results showed significant positive associations between ED and dysfunctional parenting behavior (p < .001), overreactivity (p < .001), and laxness (p < .01) and negative associations with warmth (p < .01). These associations varied across the dimensions of ED examined. Regression analyses were run to examine the unique effects of ED (separate models for overall and specific dimensions) and psychological symptoms; overall ED and its dimensions accounted for significant variance in parental behaviors (R2 = .10-.24, p’s < .01), while additional model steps including psychological symptoms were not significant except for the association between depression and lower warmth. In efforts to reduce the intergenerational effects of trauma, parenting interventions that include a direct focus on certain dimensions of ED may be critical.